The factors that influencing employees’ job satisfaction in Felda Wilayah Kuantan / Mohd Haziq Roslan - Roslan, Mohd Haziq (Faculty of Business and Management, 2013)
The purpose of this study is to examine the factors that influencing employees’ job satisfaction in Felda Wilayah Kuantan. Job satisfaction can be defined as a "person's feelings of pleasure or disappointment resulting from comparing a product's perceived performance (or outcome) in relation to his or her expectations on their job. A total of 85 respondents from Felda Wilayah Kuantan office were participated in answering questionnaire. The findings of the study indicate that there is significant relationship between pay and promotion, job securities and relationships with co-worker and employee’s job satisfaction in this organization. However the most influence factors that influences employee’s job satisfaction in this organization is pay and promotion. The problem statement for this study is about effect from each factor that influences employee’s performance, quality of worker and quality of management in organization. Research paper has been choosing to complete this study.